A sick day for amos mcgee eaudiobook (caldecott medal winner). - Stead, Philip C. (Macmillan Young Listeners, 2017)
THE BEST SICK DAY EVER and the animals in the zoo feature in this striking picture book debut. Friends come in all sorts of shapes and sizes. In Amos McGee's case, all sorts of species, too! Every day he spends a little bit of time with each of his friends at the zoo, running races with the tortoise, keeping the shy penguin company, and even reading bedtime stories to the owl. But when Amos is too sick to make it to the zoo, his animal friends decide it's time they returned the favor. A Sick Day for Amos McGee by Philip C. Stead and Erin E. Stead is a 2011 Bank Street - Best Children's Book of the Year and the winner of the 2011 Caldecott Medal. This title has Common Core connections.